Theory of legal act and the concept of legal business - Roque Montesillo, Luz Gladys (2008)
This article has the purpose of making the theory of the legal transaction known, as well as the concept and the content of the legal business in relation to the article 140 of the Peruvian Civil Code. It aims to realize an exposition to establish which conception must be followed by the substantive civilian norm, having to consider the social reality of each legal ordering.